Big Translation History and the Use of Data Mining and Big Data Approaches: Panel Report and Observations.: (EST Congress 2019 in Stellenbosch) - Vimr, Ondřej (chronotopos – A Journal of Translation History, 2020)
This contribution is a report on the panel "Big Translation History" that took place at the Congress of the European Society for Translation Studies in Stellenbosch in September of 2019.